LANDASAN HUKUM PENDIDIKAN ISLAM DI INDONESIA - Dede Misbahul Alam; Muhammad Mujtabah; Ririn Purnamasari (STKIP Subang, 2026)
This study examines the legal foundation of Islamic education in Indonesia through an integrative approach between Islamic law (sharia) and positive law. The research reveals that Islamic education in Indonesia has a strong and comprehensive legal foundation consisting of two complementary dimensions: sharia law sourced from the Qur'an, Sunnah, and ijtihad methods (qiyas and istihsan), and positive law manifested in the 1945 Constitution, Law No. 20 of 2003 on the National Education System, and Government Regulation No. 55 of 2007 on Religious Education. Using qualitative methods with normative juridical approaches, this research finds that the relationship between sharia law and positive law is not contradictory but rather synergistic and harmonious. Both legal foundations work together to achieve the ultimate goal of Islamic education: forming insan kamil (complete human beings) who are faithful, pious, noble in character, intelligent, and competent. This study contributes to understanding how Islamic education in Indonesia successfully integrates religious values with national education systems, creating a unique model that can serve as a reference for other Muslim-majority countries. The findings show that this legal integration not only guarantees the existence of Islamic education but also provides space for innovation and development while maintaining Islamic authenticity.